Active and hybrid filters in medium voltage distribution power systems - Corasaniti, Víctor Fabián (2010)
This paper presents the design of different topologies of active power filters to compensate reactive power and harmonics in the medium voltage level of a distribution power system. One pure active filter and two hybrid topologies, are implemented. A pure active compensation is obtained with a Shunt Active Power Filter (SAPF). The shunt combination of SAPF and passive filter, form one of the hybrid topologies implemented, named Shunt Hybrid Active Power Filter (SHAPF). The other hybrid topology, called Hybrid Shunt Active Power Filter (HSAPF), connects the active filter in series with two shunt passive filters. The control algorithm are implemented with the d-q theory measuring the system current to compensate the load, setting a feedback control loop, rather than a simple feedforward compensation. Simulation for different load demands and distortions are performed. Finally a comparative evaluation of the different filters is carried out.